Large Polycyclic Aromatic Hydrocarbons as Graphene Quantum Dots: from Synthesis to Spectroscopy and Photonics. Issue 23 (11th July 2021) - Paternò, Giuseppe Maria; Goudappagouda,; Chen, Qiang; Lanzani, Guglielmo; Scotognella, Francesco; Narita, Akimitsu
Abstract: Synergistic research efforts in multistep chemical synthesis and state‐of‐the‐art optical spectroscopy have permitted the realization of graphene quantum dots (GQDs) with defined structures and properties, paving the way towards their possible applications in photonics and optoelectronics. One such fruitful feedback loop between synthesis and spectroscopy is represented by the recent development of stable GQDs with zigzag edges, displaying excellent spectral features such as optical gain and strong absorption/emission in the visible/near‐infrared regions, which are appealing for applications in photonics. In this progress report, the authors provide an overview of the latest developments in the chemical synthesis and advanced spectroscopic investigations of atomically precise GQDs, with particular emphasis on those with zigzag‐edged structures. The latest developments in their applications are also introduced, for example, in lasing and optical imaging, and new opportunities in the field of GQDs are discussed, including chiral GQDs with chiroptical properties and possible applications of GQDs for long‐lived luminescence. The authors highlight the role and power of chemical synthesis and spectroscopy in providing new GQDs with promising optical properties that pave the way for new and exciting applications in photonics. Abstract : This article provides an overview of the latest developments in the synthesis and spectroscopic investigations of large polycyclic aromatic hydrocarbons, which are graphene quantum dots with atomically precise chemical structures. Particular emphasis is given on their high potentiality for photonic applications, such as lasing, imaging, and afterglow emission, as well as a new application avenue as chiroptical materials.